Dispositivos contemporáneos de visibilización, reconocimiento y registro de pueblos originarios en la Provincia de Santa Fe - Gomitolo, Mercedes Sofía (Universidad Nacional del Litoral, 2021)
The article discusses the implications of some state devices in the terms of visibilization, recognition and restitution of lands of indigenous re-emergency processes in the province of Santa Fe. Particularly, we make a distinction between the active nature of census, legal status, the Special Registre of Aborigeans Communities and the registration and grant of land plots in the setting of a process of etnic re-emergency “territorially controlled” by the State. To the analysis we used statistics, reports and official documents (provincial and nacional) through which is made visible/invisible, registers, support discourses about santafesinian indigenous people and their conditions to action.